Does Family Involvement Make Firms Donate More? Empirical Evidence From Chinese Private Firms. (September 2014) - Dou, Junsheng; Zhang, Zhongyuan; Su, Emma
This article follows recent development on the socioemotional wealth perspective to examine the impact of family involvement on corporate charitable donations. Based on data collected from 2, 821 Chinese private firms, we find that (a) family ownership and the duration of family control positively affect charitable donations and (b) when the next generation is unwilling to take over the business, the positive relationship between family ownership and charitable donations becomes weaker. These findings show that firms' proactive stakeholder engagement is susceptible to family involvement. They also highlight the possible existence of the "dark" effect of certain socioemotional wealth dimensions on firms' proactive stakeholder engagement.